University education in times of covid-19: relationship between virtual modality and addressing student risk - Borbón-Morales, Carlos Gabriel; Laborín Álvarez, Jesús Francisco; Vera Noriega, José Ángel; Araiza Sánchez, Luis Manuel (Areté, Doctorate in Education Digital Journal, 2024)
The objective was to evaluate the coping with extreme risk of a group of university students from the state of Sonora, Mexico, in the post-pandemic era with virtual classes. The methodological strategy consisted of a non-experimental, relational design. 204 university students participating in degrees in health sciences, economics-administration and engineering from two public universities participated. The scale for coping with extreme risks was used, grouping two coping styles: active and passive. An exploratory factor analysis and internal consistency index were estimated. The correlation between the positive factors was .462 and for the negative ones it was .303. 10 items were eliminated because they did not contribute to the measurement of the construct. The total explained variance was 34.7 and the reliability of the total scale was .70. Students show a strong tendency to face problems directly, consistent with active coping, which places them in the positive dimensions of highest effectiveness in coping with extreme risks. The dimensions of activity regulation and cognitive control and planning are therefore the most expected. On the opposite level, to a lesser extent they presented behaviors in the dimensions of distraction and denial in the rejection strategy, whether positive or negative, as indicated in positive distraction that refers to social support.